Results of manipulation of idiopathic clubfoot deformity in Malawi by orthopaedic clinical officers using the Ponseti method: a realistic alternative for the developing world? - Tindall, A; Steinlechner, C; Lavy, C; Mannion, S; Mkandawire, N (2005)
This study looks at whether orthopaedic clinical officers, a cadre of clinicians who are not doctors, can effectively manipulate idiopathic clubfeet using the Ponseti technique. One hundred consecutive cases of uncomplicated idiopathic clubfeet in newborn babies were manipulated by orthopaedic clinical officers. Fifty-seven of these were fully corrected to a plantigrade position by Ponseti manipulation alone, and a further 41 were corrected by manipulation followed by a simple percutaneous tenotomy. Orthopaedic clinical officers therefore corrected 98 out of 100 feet; the remaining 2 feet were referred for surgical correction. This shows that the Ponseti method is suitable for use by nonmedical personnel in the developing world to achieve a plantigrade foot.